‘Firing cannons to kill mosquitoes' : Controlling virtual ‘streets’ and the ‘image of the state’ in Bangladesh - Lacy, Mark; Mookherjee, Nayanika (Contributions to Indian Sociology, 2020)
This article examines the historical, social and political legacies of the Information and Communication Technology Act (ICT Act) (2006–2018, amended in 2013) and the Digital Security Act (DSA) (2018–) in the Bangladeshi state’s attempt to control the virtual ‘streets’ of Bangladesh. The application of ICT and DSA has become an increasingly visible and controversial means to provide the spectacle of a state that extends disciplinary power and governmentality into proliferating online spaces—akin to ‘Firing cannons to kill mosquitoes’. We use the lens of Tim Mitchell’s structural-effect (1991, The American Political Science Review 85(1), 77–96) to understand the state beyond the frameworks of its salience or elusiveness, arguing that the criminalisation of online speech has enabled the creation of ‘digital vigilantes’ who are predominantly the powerful, the sycophants, a multitude of attention seekers who are driven by their personal contestations and ambitions. The legal outcomes, however, have been more ambiguous and uncertain—but the effect is to produce fear as an ‘environment’ (Virilio 2012, The Administration of Fear. Cambridge, MA, The MIT Press) through frozen/suspended charges with the potential to be redeployed in different contexts.
EPrint Processing Status: Full text deposited in DRO